Functional behavior and gene expression of magnetic nanoparticle-loaded primary endothelial cells for targeting vascular stents. (May 2015) - Zohra, Fatema Tuj; Medved, Mikhail; Lazareva, Nina; Polyak, Boris
Aim: To assess functional competence and gene expression of magnetic nanoparticle (MNP)-loaded primary endothelial cells (ECs) as potential cell-based therapy vectors.Materials & methods: A quantitative tube formation, nitric oxide and adhesion assays were conducted to assess functional potency of the MNP-loaded ECs. A quantitative real-time PCR was used to profile genes in both MNP-loaded at static conditions and in vitro targeted ECs.Results: Functional behavior of MNP-loaded and unloaded cells was comparable. MNPs induce expression of genes involved in EC growth and survival, while repress genes involved in coagulation.Conclusion: MNPs do not adversely affect cellular function. Gene expression indicates that targeting MNP-loaded ECs to vascular stents may potentially stimulate re-endothelialization of an implant and attenuate neointimal hyperplasia.